EXPRESSION OF ISOCITRATE DEHYDROGENASE 1 MUTATION BY R 132 H ANTIBODY CLONE H09 IN GRADE II-IV ASTROCYTOMA AND SECONDARY GLIOBLASTOMA - PRAGNYA PARAMITA MISHRA; TAPAS RANJAN MISHRA; PRIYA KUMARI; PREMANAND PANDA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Based on their development patterns, behaviors, and shared genetic driver mutations in the isocitrate dehydrogenase (IDH1) and IDH2 genes, diffusely infiltrating gliomas are categorized. There are three types of astrocyte tumors: Not otherwise specified (NOS), IDH-mutant, and IDH-wildtype. About 10% of cases of low-grade glioma that arise in young people and have an IDH1 mutation progress to secondary glioblastoma (sGBM). Hence, IDH sequencing is highly recommended. The aim of the study is to show the presence of IDH1 mutation in all grades of astrocytomas and sGBM and classify them using IDH1 mutation as per the new World Health Organization central nervous system classification. Methods: The study was conducted in the Department of Pathology, Hitech Medical College and Hospital, Rourkela and was a single-center prospective cross-sectional study that started in January 2023 and ended in December 2024. Paraffin-embedded tissue sections were subjected to immunohistochemistry (IHC) using IDH1 R 132 H CLONE H09 as per standard protocol, and slides were studied. All patients are followed through telephonic conversation. Results: A total of 47 cases were received over the study period. Out of the total cases, 60% of grade 2 astrocytoma and 50% of cases of grade 3 astrocytoma are IDH1 positive. Of 24 cases of grade 4 astrocytoma, one case is IDH1 positive, whereas all 03 cases of sGBM are positive. Statistically significant results were obtained in the distribution of tumors and IDH1 mutation positivity in grade 4 astrocytoma. Conclusions: Classified astrocytomas into IDH mutant and wild-type categories, thereby reducing NOS categories. IDH1 IHC is considered a surrogate marker in assessing the IDH1 mutational status.